Pengabdian Mandiri Kemitraan Masyarakat Pendampingan Akuntansi Sederhana untuk Mendukung Kualitas Layanan pada Tenank Cafe Medan - Muhammad Zuardi; Sally Maya Vida; Raina Rosanti; Sabarita Tarigan; Heddy Heddy (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting national economic growth, particularly in the culinary sector. However, many MSME entrepreneurs still face challenges in financial management due to the lack of proper implementation of simple accounting systems. Tenank Cafe Medan is one of the culinary businesses with strong growth potential, yet it continues to experience difficulties in transaction recording, cash flow management, and the preparation of simple financial statements, which affect the quality of business services. Therefore, this Community Partnership Independent Service Program (PMKM) aims to provide assistance in simple accounting practices to improve service quality at Tenank Cafe Medan. The program was implemented through observation, socialization, training, direct practice, and mentoring activities. The materials included transaction recording, cash book preparation, simple income statements, and cash flow management. The results show an improvement in the partner’s understanding and ability to manage finances systematically. Better financial management has also contributed to improving operational management and customer service quality. Thus, this program positively supports business management strengthening and service quality improvement at Tenank Cafe Medan.